Notes about the communications Mokri do–Diluntum with sideways settlements - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This work presents the communication data Mokri do–Diluntum with sideways settlements. From the station Leusinium  (Panik), the road went north to the place Mokri do, where it was divided into two directions. One direction was west over Plana, Orahovice, Berkovići to Diluntum.  The second one was north into the interior of Dalmatia province over Gacko to Podrinje. Archeological finds from the south of Dalmatia province (eastern Herzegovina) shows that network of Roman communications was developed very early in this area. This work presents facts about the new outfield observations about the remains of the roads and settlements Plana, Orahovice, Fatnica in this area, too.
Keywords: Diluntum; Mokri do; Southern Dalmatia; Eastern Herzegovina; settlements; communication